Anisakis physeteris Baylis - Luque, José L.; Muniz-Pereira, Luís C.; Siciliano, Salvatore; Siqueira, Liege R.; Oliveira, Magda S.; Vieira, Fabiano M. (Zenodo, 2010)
Anisakis physeteris Baylis Balaenoptera borealis (Lesson), unspecified site of infection, unspecified locality (Pinto et al. 2004). Balaenoptera physalus (Linnaeus), unspecified site of infection, unspecified locality (Pinto et al. 2004). Kogia breviceps (Blainville), stomach, Fernando de Noronha Archipelago, Rio de Janeiro (Santos & Lodi 1998; Pinto et al. 2004) (CHIOC 33539). Physeter catodon Linnaeus, stomach, Rio de Janeiro (Muniz-Pereira et al. 1999) (CHIOC 29602, 29603, 29659, 29662, 29665 - 29667, 29669, 29670, 29691). Published as part of Luque, José L., Muniz-Pereira, Luís C., Siciliano, Salvatore, Siqueira, Liege R., Oliveira, Magda S. & Vieira, Fabiano M., 2010, Checklist of helminth parasites of cetaceans from Brazil, pp. 57-68 in Zootaxa 2548 on page 60, DOI: 10.5281/zenodo.196777